Finding appropriate techniques in translating Sundanese terms of address - Sukaesih, Ina; Purwaningrum, Endang; Indrayani, Septina (Journal of Applied Studies in Language, 2021)
The research addresses how Sundanese terms of address are translated into English. It discusses specifically the translation techniques practiced by the translator which affect the quality of the translation. The data are taken from Sundanese short stories and their translation in English. The theories exercised to find out the applied techniques are based on Molina and Albir (2002). The translation quality is examined using translation quality assessment of Nababan et al (2012). The analyses are carried out using Santosa’s methods (2017), a modification of Spreadly’s, following the analysis steps of domain, taxonomy, componential and culture findings. The results show that there are five translation techniques practiced by the translator, namely established equivalent, pure borrowings, deletion, variation, and implicit. The translation quality appears to gain 2.7. This score means that the translation is quite good. While the translation accuracy takes the highest score of 2.9, followed by acceptability 2.8, and readability having 2.5.